Implementation Of The Digital Population Identity (IKD) Service Program Policy - Pratiwi, Chandra; Khumayah, Siti (ann4publisher@gmail.com, 2026)
Background. Population administration services in Cirebon Regency are carried out in accordance with Minister of Home Affairs Regulation Number 72 of 2022, including the Digital Population Identity policy. Based on a report from the Population and Civil Registration Office of Cirebon Regency as of July 2025, the Digital Population Identity activation rate has only reached 5.06% of the established national target of 30%. This low achievement is the main focus of the study. This study aims to analyze and explain the implementation of the Digital Population Identity (IKD) service program in Cirebon Regency using the theory of George C. Edward III. The method used is a descriptive qualitative approach, with data collected through interviews and document analysis. Data validity is tested using triangulation techniques. The results show that the implementation of the Digital Population Identity policy is supported by active communication through social media and direct outreach, as well as strong commitment from implementers, since Digital Population Identity is considered a solution to the limited availability of electronic ID card blanks. However, there are still obstacles in terms of resources, such as a lack of specialized personnel and disruptions in the central server network, as well as in the bureaucratic structure, which does not yet have technical standard operating procedures (SOPs) at the local level. The study concludes that the implementation of the IKD in Cirebon Regency has not been effective. The development of specific local SOPs, an increase in the number of specialized human resources, and the strengthening of network infrastructure are required to ensure the sustainability of digital transformation.